Long COVID Oral Cavity Symptoms Based on Selected Clinical Cases - Rafałowicz, Barbara; Wagner, Leopold; Rafałowicz, Juliusz (European Journal of Dentistry, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is characterized by variable clinical features, different durations, and several previously unheard-of late complications. Knowledge about this infection is constantly evolving.The aim of the study is to present selected cases of the most common symptoms of long COVID in the oral cavity.Among the 1,256 studied patients, 32% of them had discoloration, ulceration, and hemorrhagic changes on the oral mucosa, 29.69% had mycosis located on the tongue, 25.79% of patients had aphthous-like lesions on the hard palate, and in 12.5% atrophic cheilitis was observed. During the anamnesis, approximately 60% of patients reported salivary secretory disorders in the initial period of infection, which is 6.68% prolonged up to 4 months after systemic symptoms disappeared. In an extreme case, an aphthous-like lesion was located on the hard palate, which persisted for 6 months. Approximately 36% of patients did not agree to the proposed treatment. As a result, they only received recommendations on the use of oral hygiene products and received weekly check-ups. In this group of patients, most pathological changes spontaneously cleared after 3 weeks. The elderly with coexisting diseases, persons with a more severe SARS-CoV-2, and hospitalized patients had more extensive and severe lesions in the oral cavity that persisted for a long time after infection.In patients after the SARS-CoV-2 infection and suspected of this infection, a detailed intraoral examination should be performed, and the patient must be obligatorily monitored for a minimum period of 6 months. Depending on the patient's clinical condition, changes in the oral cavity require observation, basic or specialist treatment. In the case of changes in the cavity without pain symptoms, observation should be made for approximately 4 weeks and wait for the spontaneous regression of the changes. However, when pain occurs, a good solution is to use laser biostimulation. In the case of complex pathological changes occurring in the oral cavity, the patient should be directed for specialist treatment.
Keywords: changes of mucosa; tongue; palate; cheilitis; long COVID